Quality Assurance Practices a Panacea to Effective Administration of Federal Unity Secondary Schools in North-West Zone, Nigeria - Kamalu, Alkasim; Muhammad, Shehu Yahaya (Kashere Journal of Education, 2025)
The study examined the influence of quality assurance practices on the administration of federal unity secondary schools in the northwest zone of Nigeria. Two specific objectives, research questions and null hypotheses were formulated. The study adopted a descriptive survey research design, with a population of 1,379, which included 134 quality assurance officials, 19 principals, and 1,226 teachers. A sample size of 291 was purposively drawn from this population, comprising 14 principals, 68 quality assurance officials, and 209 teachers. A structured questionnaire containing 80 items was used as the instrument for data collection. The data collected from the field was analysed using descriptive statistics (frequency, percentages, and mean scores) to describe the demographic characteristics of the respondents and answer all research questions. Inferential statistics of Analysis of Variance (ANOVA) were used to test all the null hypotheses at the 0.05 level of significance. The study concluded that quality assurance practices enhance the decision-making process in the school and influence recruitment and retention of staff, influence staff development, manage facilities in schools and influence enrolment and retention of students in federal unity secondary schools